College Teachers’ Involvement in the Promotion of Information Literacy (British Journal of Multidisciplinary and Advanced Studies, 2023)
Information literacy is an important skill student must gain, and college teachers are major contributor to this independent lifelong learning and enhance students' library engagement. This study attempted to establish that college teachers’ involvement in the promotion of information influenced students' library engagement.  This assumption was verified in one of the higher educational institutions (HEIs) in the Southern part of Bukidnon, Philippines. A concurrent nested mixed method research design using one modified survey questionnaire on the constructs was the main primary source of the quantitative and qualitative data. Three hundred twenty-eight (328) students from one of the HEIs participated and assessed their respective college teachers' involvement in promoting information literacy. Participants were college students scheduled to get their modules from their teachers during the school year 2021-2022. Descriptive statistics, and regression analysis used and complemented with qualitative data from students. The study revealed that teachers' involvement is a significantly influences student engagement in the library. This study hopes to contribute to the scanty research in the Philippines that focused on the involvement of college teachers in promoting